Proceedings of the Eighth Conference on Participatory Design Artful Integration: Interweaving Media, Materials and Practices - 2004
DOI: 10.1145/1011870.1011885
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating collaboration through design games

Abstract: In recent years both companies and research communities call for collaborative work practices and user-centered approaches in various design fields. There are several challenges and issues to take into consideration. For instance there is a need to find ways of collaborating across various competences, interests, responsibilities and perhaps professional languages both within one organization, between several organizations and between the organizations and a group of (potential) users. It is necessary to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(155 citation statements)
references
References 20 publications
(14 reference statements)
3
135
0
8
Order By: Relevance
“…While some methods such as role-playing, make-believe, and design games are methodologies that have been available to designers for a long time (e.g. Brandt and Messeter 2004;Seland 2006), the use of game mechanics during the evaluation stages of interactive systems has not been fully investigated.…”
Section: Hci and Gamificationmentioning
confidence: 99%
“…While some methods such as role-playing, make-believe, and design games are methodologies that have been available to designers for a long time (e.g. Brandt and Messeter 2004;Seland 2006), the use of game mechanics during the evaluation stages of interactive systems has not been fully investigated.…”
Section: Hci and Gamificationmentioning
confidence: 99%
“…That is a good thing because it forces you to use a certain process." Indeed, it is shown that adding constraints to the ideation process improves its outcomes in terms of creativity and number of ideas developed [32].…”
Section: ) Strengths A) Guidance and Engagementmentioning
confidence: 99%
“…Within this field, there exists a variety of methods, techniques and events intended to inspire design participants and scaffold collaborative ideation and concept development. Such methods include inspiration card workshops [9], design games [3], and contextmapping [22].…”
Section: Co-designmentioning
confidence: 99%